Efek Bioinsektisida Biji Kecubung (Datura Metel) terhadap Mortalitas Ulat Grayak (Spodoptera Litura) - Yunita Wardianti; Lili Ulpa; Yuli Febrianti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to determine the bioinsecticide effect of amethyst seed (Datura metel) on the death of armyworms (Spodoptera litura). This type of research is an experiment with the design used is a completely randomized design (CRD) which consists of five treatments and five replications. The treatments were P0 with a concentration of 0%, P1 with a concentration of 10%, P2 with a concentration of 20%, P3 with a concentration of 30%, and P4 with a concentration of 40%. Based on the One Way Anova Test with a significance level of 5%, it shows significant results, F count (52.92)> F table (2.87). Followed by the Duncan test, the results showed that the concentration of 40% was significantly different from the concentrations of 0%, 10%, 20% and 30%. So it can be concluded that there is an effect of amethyst seeds (Datura metel) on the death of armyworms (Spodoptera litura), especially at a concentration of 40%. Keywords: Bioinsecticide, Amethyst Seeds (Datura metel), Grayak Caterpillar (Spodoptera litura), Mortality.